Structure of Endomorphism Semigroup of Endomappings of Some Particular Rooted Trees - Hossain, Mohd Altab (Journal of Bangladesh Academy of Sciences, 2015)
For an endomapping of a finite set of points lying on some rooted particular trees, endomorphism and endomorphism semigroup were studied. The main aim of this paper was to obtain the structure of the semigroup of all endomorphisms of the endomappings represented by directed graphs on particular types of rooted trees. Journal of Bangladesh Academy of Sciences, Vol. 39, No. 2, 169-175, 2015